2022
DOI: 10.1007/s11356-021-17785-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effect of diurnal temperature range and apparent temperature on cardiovascular disease among farmers in Qingyang, Northwest China

Abstract: BackgroundApparent temperature (AT) and diurnal temperature range (DTR) have been extensively used to evaluate the effects of temperature on cardiovascular disease (CVD). However, few studies have analyzed and compared their effects on CVD in less-developed, rural areas of China. Methods A case-only analysis was conducted of 43,567 cases of CVD morbidity in Qingyang (Northwest China) in 2011-2017 and the effects of thermal indicators were assessed using distributed lag nonlinear modelling and a Poisson regress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Further research indicates that the risk of non-accidental death among males is slightly higher than that among females, consistent with previous findings [ 28 , 39 ]. A study conducted in Qingyang, a city in close proximity to Xining [ 40 ], likewise revealed that males have a greater susceptibility to adverse effects in low temperature environments. This difference may be attributed to men's higher involvement in outside labour, the greater indoor-outdoor temperature difference, and demographic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Further research indicates that the risk of non-accidental death among males is slightly higher than that among females, consistent with previous findings [ 28 , 39 ]. A study conducted in Qingyang, a city in close proximity to Xining [ 40 ], likewise revealed that males have a greater susceptibility to adverse effects in low temperature environments. This difference may be attributed to men's higher involvement in outside labour, the greater indoor-outdoor temperature difference, and demographic factors.…”
Section: Discussionmentioning
confidence: 99%